Analisa terhadap Praktik Utang Piutang : (Studi Kasus Utang Uang Bayar Kopi di Dusun Dawuhan Desa Sucolor Maesan Bondowoso) - Imam Syarbini; Su'aidi (UNIVERSITAS BONDOWOSO, 2023)
Qardh is a special contract that is used to hand over assets to other people with an agreement that it must be returned the same as what was borrowed, to other people who can be billed or asked for back or in other words lend without expecting anything in return, for example borrowing money of one hundred thousand rupiahs, then it must be returned with the same. But the reality in society is different, especially in Dusun Dawuhan, Suco Lor Maesan-Bondowoso Village, borrowing money is paid for in coffee, the price of which is determined in an approximate way. In practice, person A (debtor) borrows money from person B (creditor) with an agreement according to the custom of the local hamlet, person A will pay off the money owed with coffee, the price of which is still based on estimates (speculative), for example Rp. 200.000,- per quintal. In fact, when the harvest season comes, the price of one quintal of coffee can go up to Rp. 400,000 and can go down to not even Rp. 200.000,-. Namely Rp. 150.000,- per quintal. The practice of debt receivables like this, contains Gharar, which is prohibited by Syara'. The solution is to prevent gharar buying and selling, which needs to be considered in the contract, namely the clarity of the intentions of each party in the transaction. Therefore, if these debts are used for consumptive purposes, then from the beginning of the contract, it must be clear. For example, if the money from the loan was made to buy coffee, the debtor should explain this. The items described serve as standard. However, that does not preclude free use by the debtor. So, even though the standard item described in the contract is coffee, for example, it is not a problem for the debtor to spend it on other goods. what is certain, the debtor must pay off according to the price of the goods that become the standard in the contract. If this is what is used, then what is actually owed is not money, but coffee. So, what is considered here is the power of the money when it is exchanged for goods. Thus, the debtor must later pay off according to the price of coffee that was made when paying it off. Although this does not rule out the possibility that the goods used as standards experience fluctuations. If it is more expensive, the debtor will pay more. Meanwhile, if it is cheaper, of course the creditor will get less. Thus, the rights of creditors are still protected. He still gets the principal property that he lends according to its value. On the other hand, the debtor has fulfilled his obligations because he has paid according to the standards set.